High-fructose diet-induced hypertriglyceridemia is associated with enhanced hepatic expression of ACAT2 in rats - Ichigo, Y; Takeshita, A; Hibino, M; Nakagawa, T; Hayakawa, T; Patel, D; Field, C. J; Shimada, M (Physiological research, 2019)
High levels of fructose induce hypertriglyceridemia, characterized by excessive levels of triglyceride-rich lipoproteins such as very low-density lipoprotein (VLDL); however, the underlying mechanisms are poorly understood. The aim of this short communication was to examine hepatic changes in the expression of genes related to cholesterol metabolism in rats with hypertriglyceridemia induced by high-fructose or high-glucose diets. Rats were fed a 65 % (w/w) glucose diet or a 65 % (w/w) fructose diet for 12 days. Serum levels of triglycerides, total cholesterol, and VLDL+LDL-cholesterol, hepatic levels of triglycerides and cholesterol, and ACAT2 expression at the gene and protein levels were significantly higher in the fructose diet group compared to the glucose diet group. The hepatic levels of Abcg5/8 were lower in the fructose group than in the glucose group. Serum high-density lipoprotein (HDL)-cholesterol and hepatic expression levels of Hmgcr, Ldlr, Acat1, Mttp, Apob, and Cyp7a1 did not differ significantly between groups. These findings suggest that high-fructose diet-induced hypertriglyceridemia is associated with increased hepatic ACAT2 expression.
Keywords: Sterol O-Acyltransferase; hypertriglyceridemie; exprese genu; krysa rodu Rattus; Fructose; Gene Expression; Male; Hypertriglyceridemia; Animals; Liver; Rats, Wistar; mužské pohlaví; játra; potkani Wistar; zvířata; cholesterolacyltransferasa; fruktosa; Rats